Analisis Rasio Keuangan PT. Telkom Persero, Tbk. Sebelum dan Setelah Memasuki Masa Pandemi Covid-19 - Salsabila Salsabila; Hendra Hermain (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
Financial statements are an important part for every company, because financial statements are records that contain information relating to the financial condition of a company. Therefore, various financial statement analyzes are needed, one of which is the company's financial ratio analysis which looks at the company's health condition based on existing financial ratios. PT Telkom Indonesia or PT Telkom Persero Tbk. Is one of the state-owned enterprises (State-Owned Enterprises) which is engaged in services, namely information and communication technology services. PT Telkom Persero Tbk always publishes financial reports and can be accessed directly through www.idx.co.id . And with the financial statements, an analysis of the financial ratios of PT Telkom Persero Tbk can be made by calculating the financial ratios needed to see its financial condition. Keywords: Financial Statements, Financial Ratio Analysis, PT Telkom Persero, Tbk